Urban ruination and the social geography of cities: some findings from the Lisbon metropolitan area - Brito-Henriques, Eduardo (2017)
The ruination of the urban built environment is intuitively associated with areas of poverty and social deprivation in cities. The Chicago School’s theories on the city growth developed in the Interwar period of the 20th century have largely supported this belief. Ruination was presented in those theories as a 'natural' result of the centrifugal growth of cities, i.e. social mobility and suburbanization. In this paper, we are going to investigate the above-mentioned relationships between the deterioration of the built environment and the social geography of cities. We seek to ascertain whether the ruins may be simply seen as inscriptions of poverty in the cityscape or whether they are signs of social and economic changes in a broader sense. Through remote sensing supported by high-resolution aerial photography and fieldwork, all the ruined buildings situated in the Lisbon city center and in an old industrial suburb of Lisbon’s periphery – Barreiro city – were identified. Census data on the socioeconomic conditions of population was then cross-referenced and a multiple linear regression was used for determining relations between the two types of data.